Interactive Learning Media Methods In The Field Of Mechanical Engineering: A Case Study Of Engineering Drawing Subjects - Zuliansah, Rizky Adi; Qolby ‘Alya, Najmy; Aprillia, Risma; Muttaqin, Shofya Azzahra; Hamdani, Husni (Jurnal Pendidikan Teknik Mesin, 2024)
This study aims to find out whether the methods in interactive learning media that have been applied are appropriate or not. The application of interactive learning media methods to engineering drawing learning can improve learning efficiency, strengthen concept understanding and improve students' practical skills in mechanical engineering learning. This study uses a qualitative descriptive method with case studies as the main method. Data is collected through questionnaires and in-depth analysis so that it becomes a whole sentence as a whole. The results of the research that has been carried out show that the most effective learning model uses the practicum model in engineering drawing subjects. In addition, teaching aids also affect students' understanding of teaching materials in engineering drawing subjects. Thus, teachers must be able to make an interactive learning so that students understand the technical drawing material to the maximum.